The relationship between self ac The relationship between self acceptance and body dissatisfaction among female adolescent Tiktok users in the city of Makassar - Firdaus, Nur Hanifah; Hamid, Harlina; ., Irdianti (Polteknik Ilmu Pemasyarakatan, 2023)
The more TikTok social media users among teenage girls, the more it will influence self acceptance of their bodies. TikTok social media can be one of the triggers for a person's dissatisfaction with their body shape due to visual content that influences the individual. This research aims to find out the relationship between self acceptance and body dissatisfaction in teenage girls who use TikTok in the city of Makassar. The research method used is a quantitative research method. The subjects in this research were teenage girls using the social media TikTok aged 11-18 years and domiciled in the city of Makassar (N = 400) who were obtained using accidental sampling techniques. Research data was tested using the Spearman rank correlation test. The measuring instruments used are the self acceptance scale and the body dissatisfaction scale. The results of the research show that there is a negative relationship between self acceptance and body dissatisfaction among teenage girls who use TikTok in the city of Makassar, amounting to (r) -0.868 with a significance level of 0.000. This research illustrates that the higher self-acceptance, the lower body dissatisfaction. The results of this research contribute to adolescent girls increasing positive self acceptance so that they can accept their bodies, thereby reducing the risk of negative things occurring due to a lack of self acceptance, one of which is body dissatisfaction. Teenagers can start by using TikTok social media wisely so that it has a positive effect on themselves. The conclusion is that from the research results, it was found that there was a negative relationship between self-acceptance and body dissatisfaction in teenage girls who use TikTok in Makassar city.